Biogas as alternative SOFC fuel: Research and implementation - Arifin N.A.; Steinberger-Wilckens R.; Shamsuddin A.H. (Institute of Physics Publishing, 2023)
Agricultural robots; Hydrogen fuels; Investments; Economic study; Green technology; IS technologies; Low emission; Micro gas turbines; Payback periods; Renewable energies; Technology implementation; Biogas